Low Anterior Resection Syndrome: Pathophysiology, Risk Factors, and Current Management - Seung Mi Yeo; Gyung Mo Son (The Ewha Medical Journal)
Low anterior resection syndrome (LARS) is a condition of anorectal dysfunction that occurs frequently following anal sphincter-preserving surgery for rectal cancer and can reduce the quality of life. In this review, we summarize the main symptoms and pathophysiology of this syndrome and discuss the treatment approaches. Early evaluation and initiation of appropriate treatment postoperatively are crucial. The most frequently used tool to evaluate the severity of LARS is the LARS score, and an anorectal manometer is used for objective evaluation. LARS is believed to be caused by multiple factors, and some of its causes include direct structural damage to the anal sphincter, damage to the innervation, loss of rectoanal inhibitory reflex, and decreased rectal volume and compliance. Diet modifications, medications, pelvic floor muscle training and biofeedback are the primary treatments, and rectal irrigation can be added as a secondary treatment. If LARS symptoms persist even after 1 to 2 years and significantly reduce the quality of life, antegrade irrigation, sacral nerve stimulation or definitive stoma may be considered. High-quality evidence-based studies on LARS treatment are lacking, and randomized controlled trials aimed at developing severity-based treatment algorithms are needed.